Pengaruh Pengetahuan Bencana Banjir Terhadap Sikap Kesiapsiagaan Masyarakat - Marlina Susilawati; Muzani Jalaluddin; Ilham Badaruddin Mataburu (Jurnal Penelitian Pendidikan Geografi, 2025)
Flooding has become a serious problem for the residents of Kebon Baru Subdistrict due to its hazardous and detrimental impacts and its nearly annual occurrence. This study aimed to identify the influence of flood disaster knowledge on community preparedness attitudes in Hamlet 10, Kebon Baru Village. The sample consisted of 100 respondents spread accros Neighbourhood 08, Neighbourhood 09, and Neighbourhood 10. Data analysis using simple linear regression with SPSS and revealed a significant influence of flood disaster knowledge on preparedness attitudes. The regression equation obtained was Y = 0.232 + 0.585X, with a coefficient of determination (R²) of 0.468, indicating that flood disaster knowledge explained 46.8% of the variability in preparedness attitudes. The F-test yielded a significance value of 0.00, while the T-test showed a T statistic of 9.286 with a significance of 0.00. These results indicated a significant positive effect of flood disaster knowledge on preparedness attitudes. The average score for community knowledge was 71.4 (moderate category), while the average preparedness attitude score was 65.5 (prepared category). These findings suggested that increased knowledge of flood disasters contributed to better preparedness in facing such events.